2022
DOI: 10.3390/children9121954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Single and Multiple Drug Hypersensitivity in Children: A Tertiary Care Center Retrospective Study

Abstract: Drug hypersensitivity reactions (DHRs) are a type of adverse drug reactions with heterogeneous pathophysiological mechanisms and a broad spectrum of clinical manifestations. Since over-diagnosing is common in children, a complete allergy work-up is needed. A cross-sectional study was conducted at a tertiary care institution, covering the five-year period. Five hundred and four patients of both sexes, mean age 7.5 and with a medical history suggestive of DHR were evaluated. ENDA/EAACI guidelines were used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Milosevic et al (16) reported that DHRs could be confirmed in 4.4% of patients presenting with suspicion of DHRs. Similarly, in our study, drug allergy could be confirmed in 4.9% of the reactions with drug allergy tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milosevic et al (16) reported that DHRs could be confirmed in 4.4% of patients presenting with suspicion of DHRs. Similarly, in our study, drug allergy could be confirmed in 4.9% of the reactions with drug allergy tests.…”
Section: Discussionmentioning
confidence: 99%
“…The low frequency of confirmed DHRs in studies conducted in patients presenting with suspected DHRs emphasizes the importance of diagnostic drug tests (15,16). Because many untested children with suspected DHRs may be incorrectly identified with drug allergy labels, which may lead to the unnecessary use of broad-spectrum, less-effective, and/or more expensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, basophils and mast cells are stimulated to release inflammatory mediators by IgE mediation, but other mechanisms are also known, such as non-IgE and non-immune activation of mast cells. According to Milosecic K. et al, the most common manifestation of drug hypersensitivity in children was acute urticaria (78.2%), followed by exanthema (10.5%) and angioedema (5.3%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigating DHR in children was conducted in Serbia ( 10 ). They evaluated 504 patients, with a mean age of 7.5 years.…”
Section: Epidemiology Of Drug Allergy In Childrenmentioning
confidence: 99%
“…Urticaria was the most common skin manifestation (78.2%), followed by exanthema (10.5%) and angioedema (5.3%). The presence of extracutaneous manifestations was significantly associated with a positive allergy test ( p = 0.022, OR 4.62, 95% CI 1.05–15.76%) ( 10 ).…”
Section: Epidemiology Of Drug Allergy In Childrenmentioning
confidence: 99%